Molecular-physiological response of oil palm seedlings to drought stress and functional characterization of Egdreb1 in transgenic tomato - Mohammad Azzeme, Azzreena (2015)
Drought is an insidious natural hazard that imposes serious challenges to agricultural activities in the world. It causes losses of major food crops, interfering food chains and losses of world economic worth of million dollars every year. In Malaysia,climate change such has El Nino has become a major problem that gives negative impact to environment. El Nino has an ability to bring worst drought phenomena. Apart from that, even though Malaysia receives an average rainfall of 2000 mm annually, there are certain areas still have low amount of rainfall such as Kedah and Perlis. The low rainfall period can prolong up to two to three months. Thus, it may give negative impacts to oil palm (Elaeis guineensis Jacq.) plantation, because adequate water is essential for healthy growth and maximum performance of oil palm seedlings. Therefore, this study was conducted to determine physiological and molecular changes of oil palm seedlings in response to different severity of drought stress. To achieve the objective, a study that links the symptoms under different drought severity with physiological and molecular responses was carried out. Five durations of drought treatments (7, 14, 21, 28, 35 days of water withholding; DWW) were given to 5-month-old seedlings. The necrosis, chlorosis and burned symptoms started to appear in seedling leaves at 21 DWW (severe drought). However, the leaf physiological data showed photosynthetic rate (A), stomatal conductance (gs) and transpiration rate (E) started to decrease earlier as at 7 DWW (mild drought) before any stress morphological symptoms in leaves were established. Drought-responsive element binding 1 (DREB1) belongs to AP2 superfamily of plant specific transcription factor (TF). Early accumulation of the oil palm EgDREB1 transcript (>1-fold) in roots might be associated with signaling pathway; while the significant up-regulation of EgDREB1 in leaves under severe drought corresponded to the high peroxidase (POD) antioxidant gene expression in roots. Catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX) and glutathione reductase (GR) antioxidant genes which were highly up-regulated under moderate drought in leaves may be involved in scavenging reactive oxygen species (ROS) and ensuring water balance in this tissue. The ethylene responsive binding protein (EREBP), late embryogenesis abundant (LEA), dehydrin (DHN), cold-induced (CI), heat shock protein 70 (HSP70) and metallothionein type 2 (MET2) were differentially upregulated in the leaves, while in roots only the LEA protein genes (LEA and DHN) were up-regulated. The diminishing total chlorophyll (chl) content and the ratio of chla to chlb (chla:chlb) were significantly observed (P<0.05). The significant reduction of chla was closely related to the deficiency of photosystem II (PSII). The proline content increased gradually in both vegetative tissues, while the total soluble protein content was affected by increasing drought severity. The activity of the antioxidant enzyme, catalase (CAT; EC 1.11.1.6) was the highest in the root under severe drought stress, while guaicol peroxidase (POD; EC 1.11.1.7) activity was shown to be the highest in the leaves under mild drought stress. The full amino acid sequence of the EgDREB1 was more closely related to the dicot NtDREB2. The subcellular localization, in vivo and in vitro DNA-protein binding assays further confirmed the function of EgDREB1 protein as a transcription factor (TF). Functional analysis was carried out in tomato by over-expressing EgDREB1, driven by a constitutive double cauliflower mosaic virus 35S promoter. The in vitro T0 transgenic plants showed slower growth and dwarf phenotype under controlled conditions (24ºC), and they produced parthenocarpic fruits and fruits with reduced seed numbers when grown in the transgenic greenhouse at ambient temperature (28-30ºC) with direct sunlight even though they recovered from dwarfism symptom. Expression of EgDREB1 was high in all transgenic fruits, but not detected in the leaves and roots. The expression of ethylene-responsive genes (LeACS, LeACO and LeAP2), jasmonate-responsive genes (LeAOS and LeAOC), auxin-responsive genes (LeARF8 and LeAux/IAA), cytokininresponsive genes (LeSlCKXI and LeSlIPT1), GA-responsive gene (LeGA2ox2 and LeGA20ox4) and ABA-responsive gene (LeAAO) was regulated in a different manner between the seedless and low seed number phenotypes. This suggests the complex interplay between the different phytohormones in contributing to the abnormal fruit phenotype. EgDREB1 transgene and endogenous SRGs like LePOD, LeAPX, LeGP,LeCAT, LeHSP70, LeLEA, LeMET2, LePCS, LeSOD, LeGR, LeAAO and LeECD were up-regulated in all seedlings of T1 transgenic progeny under polyethylene glycol (PEG) treatment and cold stress (4ºC). Hence, based on these findings, EgDREB1 might be involved in fruit and seed development, leaves formation,internodes elongation and adaptation to drought and cold stress.